(untitled) (American Journal of Islam and Society, 2009)
Political Islam has been under the scholarly spotlight for over two decades. The events in the Muslim heartlands and beyond have caused scholars to critically investigate the relationship between religion and politics throughout the era of secularism; some arguing that religion is on its way out, and others stating that it is gradually gaining ground in the public arena. For the western-trained scholar, the religion-politics divide is a sine qua non; however, for those outside the scholarly circles, religion has always been connected to and intertwined with politics. This has been the case with Islam. The editors of this text, which focuses on the nature of political Islam and the nation-state on the African continent, have brought together a crop of scholars with divergent views. It consists of nine chapters, an introduction coauthored by Hussein Solomon and Akeem Fadare, and a conclusion coauthored by Solomon and Firoza Butler ...